Seasonal abundance and habitat use of bird species in and around Wondo Genet Forest, south‐central Ethiopia. Issue 10 (4th April 2017) - Girma, Zerihun; Mamo, Yosef; Mengesha, Girma; Verma, Ashok; Asfaw, Tsyon
Abstract: The habitat use and seasonal migratory pattern of birds in Ethiopia is less explored as compared to diversity studies. To this end, this study aimed at investigating the patterns of distribution related to seasonality and the effect of habitat characteristics (elevation, slope, and average vegetation height) on habitat use of birds of Wondo Genet Forest Patch. A stratified random sampling design was used to assess the avian fauna across the four dominant habitat types found in the study area: natural forest, wooded grassland, grassland, and agroforestry land. A point transect count was employed to investigate avian species richness and abundance per habitat type per season. Ancillary data, such as elevation above sea level, latitude and longitude, average vegetation height, and percent slope inclination, were recorded with a GPS and clinometers per plot. A total of 33 migratory bird species were recorded from the area, of which 20 species were northern (Palearctic) migrants while 13 were inter‐African migrants. There was a significant difference in the mean abundance of migratory bird species between dry and wet seasons ( t = 2.13, p = .038, df = 44). The variation in mean abundance per plot between the dry and wet seasons in the grassland habitat was significant ( t = 2.35, p = .051, df = 7). In most habitat types during both dry and wet seasons, omnivore birds were the most abundant. While slope was a good predictor for bird species abundance in the dry season, altitude and average vegetation height accounted more in the wet season. The patch of forest and its surrounding is an important bird area for migratory, endemic, and global threatened species. Hence, it is conservation priority area, and the study suggests that conservation coupled with ecotourism development is needed for its sustainability. Abstract : A total of 33 migratory bird species were recorded from Wondo Genet Forest Patch, southeastern Ethiopia, of which 20 species were northern (Palearctic) migrants and 13 were inter‐African migrants. There was a significant difference in the mean abundance of migratory bird species between dry and wet seasons ( t = −2.13, p = .038, df = 44). The variation in mean abundance per plot between the dry and wet seasons in the grassland habitat was significant ( t = −2.35, p = .051, df = 7).